2020
DOI: 10.34172/mj.2020.078
|View full text |Cite
|
Sign up to set email alerts
|

Short and long-term mortality in severe sepsis/septic Shock in a setting with low antibiotic resistance centers

Abstract: Background: Sepsis, which is a common inflammatory response to severe infection, is one of the major causes of mortality in hospitalized patients. Sepsis, severe sepsis or sepsis syndrome, and eventually septic shock, may be seen in the development of infection. The aim of this study was to evaluate the short-term and long-term mortality in patients with severe sepsis and septic shock in centers with low antibiotic resistance. Methods: In this cross-sectional study, blood culture samples and peripheral blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Population-based national mortality registries have also shown supporting data, for instance Weng et al found that comorbidities increase mortality from sepsis, independent of other variables [24]. In addition, different studies have shown that kidney injury [25] and heart failure [14,26] are prominent factors independently associated with mortality in patients with sepsis. In our study, in agreement with these studies, the presence of chronic heart failure, cardiovascular failure, renal failure and the number of organ failures on the first day of admission were found to be associated with an elevated risk of mortality.…”
Section: Discussionmentioning
confidence: 85%
“…Population-based national mortality registries have also shown supporting data, for instance Weng et al found that comorbidities increase mortality from sepsis, independent of other variables [24]. In addition, different studies have shown that kidney injury [25] and heart failure [14,26] are prominent factors independently associated with mortality in patients with sepsis. In our study, in agreement with these studies, the presence of chronic heart failure, cardiovascular failure, renal failure and the number of organ failures on the first day of admission were found to be associated with an elevated risk of mortality.…”
Section: Discussionmentioning
confidence: 85%